2023
DOI: 10.3389/fmicb.2023.1187572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coal-derived compound fertilizers on soil bacterial community structure in coal mining subsidence areas

Abstract: The land damaged by coal mining can be recovered to healthy condition through various reclamation methods. Fertilization is one of the effective methods to improve soil fertility and microbial activity. However, the effects of coal-derived compound fertilizers (SH) on bacterial communities in coal mining subsidence areas still remain unclear. Here, we studied the effects on the nutrient characteristics and bacterial communities in fertilizer-reclaimed soil (CK, without fertilizer; CF, common compound fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(95 reference statements)
1
2
0
Order By: Relevance
“…The top ten clades in summer abundance were Proteobacteria , Acidobacteriota , Firmicutes , Bacteroidota , Gemmatimonadota , Actinobacteriota , Verrucomicrobiota , Desulfobacterota , Chloroflexi and Myxococcota , while the top ten clades in winter abundance were Proteobacteria , Acidobacteriota , Gemmatimonadota , Bacteroidota , Firmicutes , Acidobacteriota , Myxococcota , and Verrucomicrobiota , Chloroflexi and Desulfobacterota . This result is similar to other studies of soil microbes in coal mining subsidence areas (Meng et al 2023 ; Fang et al 2023 ). In addition, in our study, although alpha diversity analysis showed no significant difference in soil microbes between the two seasons, the summer soil microbial community annotated more OTUs and the number of OTUs specific to the two seasons far exceeded the number of shared OTUs (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The top ten clades in summer abundance were Proteobacteria , Acidobacteriota , Firmicutes , Bacteroidota , Gemmatimonadota , Actinobacteriota , Verrucomicrobiota , Desulfobacterota , Chloroflexi and Myxococcota , while the top ten clades in winter abundance were Proteobacteria , Acidobacteriota , Gemmatimonadota , Bacteroidota , Firmicutes , Acidobacteriota , Myxococcota , and Verrucomicrobiota , Chloroflexi and Desulfobacterota . This result is similar to other studies of soil microbes in coal mining subsidence areas (Meng et al 2023 ; Fang et al 2023 ). In addition, in our study, although alpha diversity analysis showed no significant difference in soil microbes between the two seasons, the summer soil microbial community annotated more OTUs and the number of OTUs specific to the two seasons far exceeded the number of shared OTUs (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, microbial diversity is directly affected by the content and presence patterns of nutrients such as nitrogen and phosphorus. For example, the application of compound fertilizer significantly increased the nitrogen and phosphorus content of coal mining collapse soil, increased soil bacterial diversity, and improved bacterial community structure (Meng et al 2023 ). Adding biochar can similarly alter the diversity of soil bacteria and fungi as well as community structure (Liu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that with the same soil type (calcareous brown soil), the nitrogen content of reclaimed soil in coal-mining areas is only 30.43% of that in cultivated soil in Shanxi Province [ 53 , 54 ]. The natural recovery rate of soil nitrogen is extremely slow [ 55 ], and the application of P. fluorescens can significantly increase the recovery rate of soil nitrogen.…”
Section: Discussionmentioning
confidence: 99%